THE GROWTH, COLLAPSE AND QUIESCENCE OF TENO VOLCANO, TENERIFE: NEW CONSTRAINTS FROM PALEOMAGNETIC DATA - Leonhardt R.; Soffel H.C. (My University, 2006)
Tenerife basically consists of three Miocene shield volcanoes, the Anaga, the Teno and Central shield, as well as the Pliocene Cañadas volcano. The temporal evolution and structural significance of each volcano with respect to the history of Tenerife is still a matter of debate. We present paleomagnetic results in order to enhance the view of the volcanic history of the Teno volcano by means of magnetostratigraphy. It is found that the initial subaerial phase shows reverse magnetizations throughout. After two major sector collapses, dominantly normally magnetized lavas extruded. Comparisons of observed magnetic polarities with the geomagnetic polarity timescale show that these volcanic activities occurred within 0.4 Myr between 6.3 and 5.9 Ma. Significantly younger flows, ~5.3 Myr old according to their radiometric age, revealed again normal polarity throughout. The absence of inversely magnetized lavas in-between the two normal periods indicates a volcanic hiatus or erosional phase. The evolutionary sequence and the estimated high production rates for the initial building phase are similar as would be expected for a hotspot volcano. The average geomagnetic field for 6.0 ± 0.2 Ma is close to an axial dipole field showing a slight far-sided/right-handed effect. The field strength, determined by Thellier-type intensity determinations, corresponds to a virtual axial dipole moment of 4.9 × 1022A m2. This value is approximately half of the present day field strength, but similar to values obtained for the mid-Miocene. It also corresponds to the proposed tertiary low-field level of the geomagnetic dipole moment. © Springer-Verlag 2006.
Keywords: ABSOLUTE PALEOINTENSITY; MAGNETOSTRATIGRAPHY; PALEOMAGNETISM; TENERIFE; TENO VOLCANO; Pliocene; Miocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен